Redesigning Kansas City’s government district using the urban-design approach of responsive environments - Abraham, Jose P. (Kansas State University, 2010)
This thesis presents a redesign of Kansas City’s downtown Government District, making use of the conceptual approach provided by Responsive Environments (1985), a manual for urban design written by architects Ian Bentley and Alan Alcock, urban designers Sue McGlynn and Graham Smith, and landscape architect Paul Murrain. “Responsive environments” are those urban places, the physical settings of which maximize usability and social value by offering a wide range of day-to-day user choices within close proximity. The authors of Responsive Environments identify seven hierarchical qualities—permeability, variety, legibility, robustness, visual appropriateness, richness, and personalization—that are said to be vital in creating responsive environments within the city. Through a literature review and critique, chapters 1 and 2 of the thesis overview Responsive Environments in terms of several major theorists of urban place making, including urban theorist Bill Hillier (1984), urban critic Jane Jacobs (1961), and urban designer William Whyte (1980). In turn, chapters 3, 4, 5, and 6 investigate the practicability of Responsive Environments as an urban design approach by applying its three larger-scale qualities of permeability, variety, and legibility to the Government District, an existing urban area in downtown Kansas City, Missouri, presently underdeveloped in terms of environmental responsiveness and a strong sense of urban place. As a means to identify strengths and weaknesses of Responsive Environments, the last chapter of the thesis critiques the resulting Government District design. The thesis concludes that Responsive Environments is a valuable design approach that offers much for strengthening the quality of urban life and urban sustainability.
Keywords: Urban Design; Placemaking; Responsive Environments; Permeability; Variety; Legibility; Architecture (0729); Urban and Regional Planning (0999)